Correlation between Immunohistochemical and Histomorphological Features of Ampullary Carcinomas: A Study on 72 Cases from a Tertiary Health Care Center - Usha Mary Abraham; Subramaniam Ramkumar (Gastroenterology Research and Practice)
Tumors involving the ampulla could be arising primarily in the ampulla or extending from the adjacent. When a neoplasm is centered primarily in the ampulla with or without periampullary mucosal involvement, it is considered a primary ampullary carcinoma. These tumors generally have a better prognosis than duodenal and pancreaticobiliary neoplasms secondarily involving the ampulla. Distinguishing between the two primary types has prognostic implications, as the pancreaticobiliary-type ampullary carcinomas are said to have a poorer prognosis than the intestinal-type. Morphological analysis alone may not suffice in this context. The role of immunohistochemistry has therefore been explored by various groups of workers. The purpose of the present study was to determine the role of morphology and cytokeratin profile in accurate typing of ampullary carcinomas as intestinal and pancreaticobiliary.